2021
DOI: 10.1101/2021.03.04.21252499
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Eight-Week Online Cognitive Training in Parkinson’s Disease: A Randomized Controlled Trial

Abstract: Background: Cognitive training (CT) has been proposed as a non-pharmacological treatment option for the frequent cognitive impairments occurring in Parkinson's disease (PD). Objective: Assess the efficacy of CT on cognitive function in PD. Methods: In this double-blind, randomized controlled trial we enrolled 140 PD patients with significant subjective cognitive complaints. In eight weeks, participants underwent 24 sessions of computerized multi-domain CT or an active control condition for 45 minutes each (n=7… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…Our results also showed that the reduction in FA in the ATR in the cognitive training group was associated with faster responses on the ToL task. Although this subsample of PD patients with a DWI scan did not show significant training-related increases in cognitive performance on the group level, our analyses in the entire sample of 140 PD patients showed positive effects of cognitive training on ToL response time, especially for the more cognitively demanding task load 4 [34]. Combining these results they suggest training-induced improvement in processing speed during executive functioning that is accompanied with an increase in intra-striatal or thalamo-striatal fibers on the individual level.…”
Section: Discussionmentioning
(Expert classified)
See 2 more Smart Citations
“…Our results also showed that the reduction in FA in the ATR in the cognitive training group was associated with faster responses on the ToL task. Although this subsample of PD patients with a DWI scan did not show significant training-related increases in cognitive performance on the group level, our analyses in the entire sample of 140 PD patients showed positive effects of cognitive training on ToL response time, especially for the more cognitively demanding task load 4 [34]. Combining these results they suggest training-induced improvement in processing speed during executive functioning that is accompanied with an increase in intra-striatal or thalamo-striatal fibers on the individual level.…”
Section: Discussionmentioning
(Expert classified)
“…Interestingly, the decrease in FA in the ATR was associated with faster responses on ToL task (although this fell just short of our multiple comparison threshold). Traininginduced faster responses on the ToL task were the main finding on the behavioral level of our randomized controlled trial [34]. Cognitive training had no effect on network topology on neither the global or subnetwork level.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Our results also showed that the reduction in FA in the ATR in the CT group was associated with faster responses on the ToL task. Although this subsample of PD patients with a DWI scan did not show significant differences in cognitive performance after training on the group level, our analyses in the entire sample of 140 PD patients showed positive effects of CT on ToL reaction time, especially for the more cognitively demanding task load 4 [34]. Combined these results are suggestive of training-induced improvement in processing speed during executive functioning that is accompanied with an increase in intra-striatal or thalamo-striatal fibers on the individual level.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, the decrease in FA in the ATR was associated with faster responses on ToL task (although this fell just short of our multiple comparison threshold). Training-induced faster responses on the ToL task were the main finding on the behavioral level of our randomized controlled trial [34]. CT had no effect on network topology on neither the global or subnetwork level.…”
Section: Discussionmentioning
confidence: 97%